Chromis abadhah (Teleostei, Pomacentridae), a new species of damselfish from mesophotic coral ecosystems of the Maldives - Luiz A. Rocha; Hudson T. Pinheiro; Ahmed Najeeb; Claudia R. Rocha; Bart Shepherd (ZooKeys)
A new species of Chromis (Teleostei, Pomacentridae) is described from four specimens collected between 95 and 110 m depth in mesophotic coral ecosystems in the Maldives, Indian Ocean. Chromis abadhah sp. nov. can be distinguished from all of its congeners by the following combination of characters: dorsal-fin rays XIII, 12–13; anal-fin rays II,11–12; pectoral-fin rays 17–18; tubed lateral-line scales 17; gill rakers 7+17–18 = 24–25; pearly white body with a large black marking covering the anterior two-thirds of the anal fin. The closest DNA barcode sequence (5.1% average uncorrected genetic distance on the mitochondrial COI gene), among those available, is Chromis woodsi, a similar mesophotic species known from the coastal western Indian Ocean (Somalia to South Africa). The new species is easily distinguished from C. woodsi by having 13 dorsal spines (versus 14 in C. woodsi), the absence of a black band on the base of the tail (present in C. woodsi), and by the genetic difference.